Fast anatomical mapping of the carina and its implications for acute pulmonary vein isolation. Issue 5 (19th July 2021) - Shin, Dong‐In; Koektuerk, Buelent; Waibler, Hans P.; List, Stephan; Bufe, Alexander; Seyfarth, Melchior; Horlitz, Marc; Blockhaus, Christian
Abstract: Background: Fast anatomical mapping (FAM) of the left atrium and pulmonary veins (PV) during PV isolation (PVI) generates anatomical information about the carina region additionally. We aimed to investigate the utility of these data in relation to conduction abilities of the intervenous carina. Methods: We investigated 71 patients with drug‐refractory atrial fibrillation (AF) who underwent first‐time circumferential PVI using an electroanatomical mapping system. Carina width between ipsilateral PV was measured using FAM and an integrated distance measurement tool. Encirclings were divided into carina ablation and noncarina ablation groups based on the necessity of carina ablation to achieve PVI. Results: In total, 142 encirclings were analyzed and first‐pass isolation was observed in 102 (72%) encirclings. Nonfirst‐pass PVI solely due to a gap on the line or persistent carina conduction was observed in 10 (7%) and 30 (21%) encirclings, respectively. Encirclings were classified into a carina ablation group (n = 30, 21%) and noncarina ablation group (n = 112, 79%). Carina width was significantly larger in the carina ablation vs nonarina ablation group (right: 11.9 ± 1.5 mm vs 8 ± 1.4 mm, P < .001/left: 12.1 ± 1.3 mm vs 8.1 ± 1.1 mm, P < .001) requiring additional carina ablation. Conclusion: Carina‐related PV conduction is a common finding after the first‐pass ablation during PVI. Measurement of carina width using FAM is feasible and its value correlates with the necessity of carina ablation to achieve PVI. Abstract : Carina conduction after pulmonary vein isolation was studied. Especially, the relation between carina width and the necessity for carina ablation was observed using routine data from an electroanatomical mapping system.